2020
DOI: 10.2147/jmdh.s267956
|View full text |Cite
|
Sign up to set email alerts
|

<p>Awareness Toward COVID-19 Precautions Among Different Levels of Dental Students in King Saud University, Riyadh, Saudi Arabia</p>

Abstract: Purpose The risk of acquiring coronavirus disease 2019 (COVID-19) among dental professionals is high because they are exposed to aerosol production and body fluids during dental procedures. Therefore, the aim of the study was to determine the level of awareness among the dental students regarding COVID-19. Materials and Methods An online cross-sectional questionnaire with three sections (knowledge, attitudes, practice) was completed by 412 postgraduate and undergraduate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
2
12
2
1
Order By: Relevance
“…However, graduates/general practitioners demonstrated significantly higher preventive awareness than undergraduates. This finding contradicts the study reported by Al-Jasser et al (2020) 28 in which postgraduate students had the highest mean knowledge ranks, followed by interns and undergraduate students. Several studies with similar outcomes are reported from Saudi Arabia.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…However, graduates/general practitioners demonstrated significantly higher preventive awareness than undergraduates. This finding contradicts the study reported by Al-Jasser et al (2020) 28 in which postgraduate students had the highest mean knowledge ranks, followed by interns and undergraduate students. Several studies with similar outcomes are reported from Saudi Arabia.…”
Section: Discussioncontrasting
confidence: 90%
“…A possible explanation could be that respiratory infections' knowledge was somewhat lower among dental professionals than the other healthcare workers, 24 even though dental care involves the patient proximity by the dental professionals. 28 Nevertheless, a sample of dental professionals in this study could correctly identify the main symptoms of COVID-19, as evidenced by multiple responses analysis in which fever, cough, shortness of breath, followed by other COVID-19 symptoms. It helps dental professionals recognize the potential risk of COVID-19 and take the possible actions in management 25 and control the spread of contagion.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…This study was conducted among the dental students hence the present study findings were not comparable. A few studies [30][31][32][33][34] from various countries had have been reported on knowledge and perceptions regarding COVID-19 among dentists.…”
Section: Discussionmentioning
confidence: 99%
“…The respondents were questions about their adherence to safety protocols, and it was noted that 93% wore PPE models and 95% maintained social distancing guidelines. These numbers indicate awareness of required measures and implementation of set standards for infection control ( 26 ). However, despite relaxation regarding dental procedures that are allowed and precautionary measures, the majority (44%) still preferred to handle only emergency cases.…”
Section: Discussionmentioning
confidence: 99%